2022
DOI: 10.1175/jcli-d-21-0689.1
|View full text |Cite
|
Sign up to set email alerts
|

The Biophysical Impacts of Deforestation on Precipitation: Results from the CMIP6 Model Intercomparison

Abstract: Deforestation can impact precipitation through biophysical processes and such effects are commonly examined by models. However, previous studies mostly conduct deforestation experiments with a single model and the simulated precipitation responses to deforestation diverge across studies. In this study, eleven earth system models are used to robustly examine the biophysical impacts of deforestation on precipitation, precipitation extremes and the seasonal pattern of the rainy season through a comparison of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Recently, the Land Use Model Intercomparison Project (LUMIP, Lawrence et al., 2016) multimodel simulations, which were part of the Coupled Model Intercomparison Project Phase 6 (CMIP6, Eyring et al., 2016), were conducted to understand the impacts of land use and land cover change (LULCC) on climate (Boysen et al., 2020; Luo et al., 2022). Boysen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Land Use Model Intercomparison Project (LUMIP, Lawrence et al., 2016) multimodel simulations, which were part of the Coupled Model Intercomparison Project Phase 6 (CMIP6, Eyring et al., 2016), were conducted to understand the impacts of land use and land cover change (LULCC) on climate (Boysen et al., 2020; Luo et al., 2022). Boysen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Land Use Model Intercomparison Project (LUMIP, Lawrence et al, 2016) multimodel simulations, which were part of the Coupled Model Intercomparison Project Phase 6 (CMIP6, Eyring et al, 2016), were conducted to understand the impacts of land use and land cover change (LULCC) on climate (Boysen et al, 2020;Luo et al, 2022). Boysen et al (2020) first utilized the CMIP6-LUMIP multimodel simulations to examine the biophysical effect of large scale deforestation and found that the impacts of deforestation vary in sign (i.e., a switch of sign from tropical warming to extratropical cooling located around 22.6°N).…”
mentioning
confidence: 99%
“…Work on average temperature and precipitation changes under LUC, mostly using idealized deforestation experiments with a background of a stationary, pre-industrial climate, has already revealed the difficulty of finding a robust signal across models in terms of patterns and at times even sign of changes. The more robust effects are in the direction of a cooling and drying effect of deforestation (Boysen et al 2020, Luo et al 2022, Yu and Leng 2022 but with disparities among models on the size and significance of these changes. Here we present results from an analysis that attempts to maximize the LUC signal: we focus on changes by the end of the century, averaged over regions where LUC differences are largest and most consistent across ESMs.…”
Section: Introductionmentioning
confidence: 99%
“…Climate models have different representations of the land surface and the biophysical responses to land cover change, leading to different simulations of the climate response to land cover change (Boisier et al 2015, Boysen et al 2020, Baker et al 2021a, Luo et al 2022, De Hertog et al 2023. Most models agree that deforestation in the tropics causes local surface warming but disagree on the magnitude of the temperature response (Winckler et al 2019b, Boysen et al 2020.…”
Section: Introductionmentioning
confidence: 99%